Bitcoin as a state reserve and the Blockchain as a guarantor of budget execution in Colombia (2022)
Bitcoin is a cryptocurrency or digital currency which has something very similar to FIAT money and is used to acquire goods and services with such asset. Its difference is that Bitcoin works in a decentralized way, meaning that there is no authority or control entity responsible for its issuance and registration of movements using "peer to peer" technology to avoid central authority or banks. The transaction management is carried out by the entire network, as Bitcoin is an open source, its design is public and since only a total of twenty-one million Bitcoin (21,000,000) can be produced, making it a valuable asset since, unlike fiat money, it is not deflationary due to its limited production and great advantages over the traditional banking system and technology. Cryptocurrencies operate under a decentralized network called "Blockchain" or blockchain which leaves a record of each transaction in the nodes that are created to perform each of them, each one becomes a participant and manager of the books of accounts of the "Blockchain" which makes it an excellent backup traceability. Businesses run on information and the faster and more accurate the better. The Blockchain is ideal to obtain that information, since it provides immediate and totally truthful data since each transaction is validated by the other nodes, always leaving a record since its entry into the network can be tracked orders, payments, accounts, production and others. It is reliable because each block is connected to the previous and the next one giving reliable information to avoid that the information can be inserted between two different blocks or that someone seeks to alter these records, you can not do it because the validation is done by the entire network under open codes.